2022
DOI: 10.1186/s12883-022-02805-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an exercise intervention on global cognition after transient ischemic attack or minor stroke: the MoveIT randomized controlled trial

Abstract: Background Patients with a transient ischemic attack (TIA) or ischemic stroke are at increased risk of developing cognitive impairment in the subacute phase. At present, the effects of exercise on cognitive functioning following a TIA or stroke are not fully known. The purpose of this trial was to investigate the effect of exercise on global cognition. Methods The MoveIT trial is a single-centre, observer-blinded, randomized controlled trial involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…Patients in the intervention group received more guidance toward achieving an active lifestyle, and more exercise training to achieve a better CRF, than patients in the control group, which may have affected the association between PSF and CRF. However, this neutral trial found no significant difference between the intervention and control groups on the primary outcome of global cognition, as assessed by the Montreal Cognitive Assessment (MoCA), or on CRF [ 19 ]. Because this trial did found a significant between-group difference in fatigue (in favor of the experimental group at 12 months), we included treatment allocation in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients in the intervention group received more guidance toward achieving an active lifestyle, and more exercise training to achieve a better CRF, than patients in the control group, which may have affected the association between PSF and CRF. However, this neutral trial found no significant difference between the intervention and control groups on the primary outcome of global cognition, as assessed by the Montreal Cognitive Assessment (MoCA), or on CRF [ 19 ]. Because this trial did found a significant between-group difference in fatigue (in favor of the experimental group at 12 months), we included treatment allocation in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment allocation turned out not to be a confounder in the association between PSF and CRF. The present study was part of a neutral trial [ 19 ]. Patients allocated to the experimental intervention received CRF, whereas the control group received motivational interview-based counselling that focused on the attainment of secondary prevention and the improvement of both lifestyle factors and physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations